One-Hour Sepsis Bundle Compliance on Serial SOFA Scores and 28-Day Mortality: A Prospective Investigation in Bekasi Regency Referral ICUs - Mega Ayu M Marina S.A; Adhrie Sugiarto; Ratna Farida Soenarto; Ahmad Irfan (CV. AKBAR PUTRA MANDIRI, 2026)
Background: Sepsis mortality remains high in intensive care units (ICUs). This study aims to evaluate compliance with the implementation of the One hour sepsis bundle and changes in SOFA scores to predict 28-day mortality rates, knowing the 28-day mortality rate and to identify strong mortality factors mortality in sepsis patients in the ICU two of Type B Hospital, Bekasi Regency. Methods: A prospective observational cohort study was conducted in the ICUs of two Type B hospitals in Bekasi Regency in 2025. Sixty adult sepsis patients with with characteristics, SOFA score, One hour sepsis bundle compliance, Temperature, Respiratory rate (RR), Capillary refill time (CRT), Lactate level examination on admission, 24th hour and 5th day. Data were analysed using bivariate analysis.Results: The 28-day mortality rate was 81.7%. Bundle compliance showed no significant correlation with SOFA score changes or 28-day mortality rates. Bivariate analysis proved that 24-hour and 5-day SOFA, 24-hour and 5-day ΔSOFA, GCS components and renal function in 5-day SOFA scoring were significantly correlated with 28-day mortality rates. Conclusion: Compliance with the One hour sepsis bundle did not significantly affect the 28-day mortality rate. 24-hour and 5-day CRT examinations, 24-hour and 5-day SOFA scoring, 24-hour and 5-day SOFA ∆, day-5 temperature examination, day-5 lactate and Δ lactate levels, SOFA GCS scoring components and renal function can affect the 28-day mortality rate of sepsis patients in the ICU of Type B Hospital, Bekasi Regency.